Rancang Bangun Sistem Informasi Penjualan Sparepart Motor Pada Bengkel Vinensi Motor Berbasis Web Sebagai Guna Meningkatkan Penjualan dan Promosi Produk - Aris Sudianto; Hamzan Ahmadi; Alimuddin Alim (Infotek: Jurnal Informatika dan Teknologi, 2020)
Vinensi Motor Workshop is a trading company engaged in the sale of spare parts such as oil, motorcycle lights, spark plugs, mirrors and others, where the promotion and sales process is still conventional. This means that customers must go to a garage to be able to make product purchases. The design of the sales information system in the Vinensi Motor workshop is a step to increase sales and product promotions so that it can benefit the workshop itself. The purpose of building this spare part sales information system is that customers can order products without having to come by Vinensi Motor workshop, the workshop can overcome the problem of product processing, order processing so as to make it easy for consumers to get information about the products available at Vinensi Motor's workshop. This system is designed using HTML, PHP using MySQL database while the editor uses Sublime text. The results of this research are the implementation of this spare part sales information system can be used as a sales promotion tool that can be accessed anywhere and anytime, the purchase process can be directly without having to come to the store, and can simplify the product purchase transaction process, so as to increase sales from the workshop Vinensi Motor itself.DOI : 10.29408/jit.v3i2.2289